The Influence of Collaborative Inquiry Learning Model and Scientific Attitudes on 4th Grade Students' Learning Outcomes in Style Material - Dinda Widyastika; Ajat Sudrajat; Abdul Murad (BIRCU, 2020)
This study aims to determine: student learning outcomes using collaborative and scientific inquiry learning model are higher than direct learning models (Direct Instruction) on style material, student learning outcomes that have high scientific attitudes are better than students who have low scientific attitudes on material style; and the interaction of collaborative inquiry learning model and scientific attitudes towards student learning outcomes in style material. This research is a quasi-experimental study. The population in this study are 28 class IV-A students and 28 class IV-B students. The sample in this study is selected by total sampling of two classes. The instrument consisted of a style of learning outcomes test in the form of multiple choice tests and a scientific attitude questionnaire. Data analysis using two-way ANAVA at the level of α = 0.05 with the help of IBM SPSS Statistics 25 and Excel 2013. The results shows that: the learning outcomes of student style material taught using the Collaborative Based Inquiry learning model 82.96 higher than the average the learning outcomes of style material using the Direct Instruction learning model of 74.67, the learning outcomes of students who have high scientific attitudes have an average of 83.67 and the learning outcomes of students who have low scientific attitudes on average 72.76, and there are the interaction between learning models and scientific attitudes in influencing student learning outcomes material style.